Analisis Kemampuan Pemahaman Konsep Matematis Siswa pada Materi Fungsi Komposisi dan Invers Berdasarkan Jenis Kelamin - Ida Nurjannah; Rizky Esti Utami; Suprihatin Suprihatin; Lilik Ariyanto (Departement of Mathematics Education, 2024)
This study aims to describe the mathematical concept understanding abilities of male and female students in solving mathematical problems on composition and inverse functions in Grade XI of SMK Negeri 2 Semarang. This research is a qualitative descriptive study. The subjects of this study were 36 students from Grade XI Marketing 1 of SMK Negeri 2 Semarang, with 2 male and 2 female students selected. The data collection techniques used in this study were written tests and documentation. The subjects were analyzed based on indicators of students' mathematical concept understanding abilities. The data analysis technique involved stages of analysis before and after fieldwork, including data reduction, data presentation, and conclusion drawing. The results of the study indicate that male students have superior mathematical understanding abilities in using, utilizing, and selecting certain procedures or operations and applying concepts or algorithms for problem-solving compared to female students.